Edukasi Investasi Saham Syariah Generasi Z SMA Islam Ahmad Yani Kabupaten Batang - Tri Joko Sulistiyanto; Arina Hidayati (Konsienti : Community Services Journal, 2023)
The service was carried out using socialization methods and trading simulations on the Indonesia Stock Exchange, discussions and evaluations for class XI IPS students of SMA Islam Ahmad Yani, Batang Regency. The theme of the dedication is Education of Generation Z Sharia Stock Investment at Ahmad Yani Islamic High School. This theme was raised to help students understand that there are various forms of investment, one of which is investing in the Indonesian Stock Exchange with investment products in the form of Islamic stocks. This service activity aims to provide understanding and skills related to the importance of investing from an early age to prepare finances for the future. The results of community service activities, there is an increase in knowledge and understanding of Islamic stock investment among Generation Z. Initially investing does not need to be expensive, it is enough with a small nominal of IDR 100,000.00 to buy Islamic shares.